Voice Of Indonesia And Sense Of Belonging In Media: A Content Analysis - Daniel Susilo; Harliantara Harliantara (Jurnal Indonesia Sosial Teknologi, 2023)
VOI (Voice of Indonesia) is a professional media in their respective field, that exists and works for Indonesian development. Their content is dominated by cultural promotion and tourism but it’s not delivered subtly. This paper would asses the sense of belonging on VOI broadcast by RRI as an English worldwide broadcast. Content analysis by Krippendorf was used as a methodology to assess the Instagram post by VOI. As a result, VOI can’t be like VICE, subtly presenting information and their dynamic of phrases. This alarms Indonesia to stand out more in international affairs; therefore Indonesia won’t be seen as a country with empty offer.